Water Quality during Rainy and Droughty Seasons based on Water Quality Index - Azhari, Nur Fatin Aliah; Mohamad Nabi, Maisarah; Ismail, Nur Farah Wahida (Multidisciplinary Applied Research and Innovation, 2023)
The water quality index (WQI) pattern is a prominent method for determining the quality of the water. Aggregation methods are used to reduce a large volume of water quality data to a single value or index. The WQI method has been used across the world to estimate water quality (surface and subsurface) using local water quality standards. Water pollution is a serious environmental issue in Malaysia because of many activities have been done by humans until the occurrence of pollution around the body of water, which affects the natural status of the lake may be in a dangerous zone of water pollution. This research was conducted to determine the sampling area in RMC lake for Water Quality Experiment, to investigate water quality parameters for five (5) water sampling location points in RMC lake during the rainy and droughty season and also to analyze water quality levels in the lake as a whole according to Water Quality Index (WQI). The best way to assess lake water quality uses the water quality index (WQI), which can determine the lake’s condition during the rainy and droughty season. WQI classification needs to do the laboratory data from the parameters which are Biochemical Oxygen Demand(BOD), Chemical Oxygen Demand(COD), Total Suspended Solid(TSS), Ammoniacal Nitrogen(AN), pH, and Dissolved Oxygen(DO). As a result, the WQI of RMC Lake was higher during the drought than during the rainy season. The RMC lake’s WQI rating during the drought was Slightly Polluted and Clean (Class II & III), with a range of 75.21 to 82.96. Many of the samples with WQI results are classified as Class II or III. During the drought, all stations were changed to Slightly Polluted status. According to the study’s findings, the water quality in the RMC lake was better in droughty than rainy season.